A PEMANFAATAN GOOGLE DRIVE SEBAGAI SARANA PENYIMPANAN DATA PENJUALAN DI PERUSAHAAN FASHION CV. XYZ BANDUNG: PEMANFAATAN GOOGLE DRIVE SEBAGAI SARANA PENYIMPANAN DATA PENJUALAN DI PERUSAHAAN FASHION CV. XYZ BANDUNG - Rahmanesa, Abdur; Supyansuri, Cahyadi; Rokayah, Siti (NIAGARA Scientific Journal, 2024)
This research aims to determine the level of success in managing sales data in the Industrial Revolution 4.0 era using Google Drive which can be accessed easily and safely by the sales support team, namely the supply chain, business commercial and business support sections at Perusahaan Fashion CV. XYZ Bandung. The method used in this research is qualitative descriptive, by distributing questionnaires to twenty-four (24) employees from the sales support team. There are five (5) indicators that are measured and form the basis of Delone and McLlean's theory, including: reliability, speed, convenience, transmission and security. From the results of the research analysis, it was obtained that the descriptive average for all indicators was 2.85 with a Likert scale of 4, which can be categorized as sales data management in the era of the Industrial Revolution 4.0 using Google Drive at Perusahaan Fashion CV. XYZ which is running well and there are still several indicators of reliability, speed and security. needs to be improved.